Code Switching and Code Mixing in Arabic on Omer Kanan's Youtube Vlog - Astari, Rika; Amina, Umnia; Irfan Faturrahman, Muhammad (Islah: Journal of Islamic Literature and History, 2023)
Vlogs are objects of linguistic studies that are by current developments, where linguistic problems also appear in human communication patterns in interacting on social media. This study aims to determine the types, factors, and functions of code-switching and code-mixing contained in Omer Kanan's vlog. This type of research is descriptive qualitative, with data collection techniques using observation, desk review, and note-taking techniques. The data analysis method uses data reduction, data presentation, and concluding. Analysis of code-switching data using Hymes theory, and code-mixing data analysis using Hoffman theory. The data source comes from 18 Omer Kanan vlogs with the following analysis results: The types of code-switching and code-mixing found were inter-sentential switching, intra-sentential switching, and emblematic switching. intra sentential code-mixing, intra lexical code-mixing, and involving change pronunciation. Factors found in the form of habit patterns and the relaxedness of the speaker in communicating, expanding the audience network, and the attitude of the speaker's religiosity. The code-switching functions found in the vlog are in the form of quotation, addressee specifications, interjection, reiteration, message qualification, and personalization. Meanwhile, the code-mixing functions found are talking about a particular topic, repetition use for clarification, and expressing group identity.